The Effects of Information and Communication Technology (ICT) on Pedagogy and Student Learning Outcome in Higher Education - Kumar, Sunil; Priyanka (EAI Endorsed Transactions on Scalable Information Systems, 2023)
Pedagogical strategies and student learning outcomes have undergone a fundamental transformation because of higher education implementing information and communication technology (ICT). This research paper explores the varied impact of ICT on pedagogy and its correlation with student learning outcomes in higher education institutions. Through a comprehensive analysis of relevant literature, empirical studies, and case examples, this study examines the ways in which ICT has reshaped traditional teaching methods and influenced student achievement. The paper begins by investigating the adoption of digital learning platforms, blended learning models, and online assessment tools in higher education settings. It delves into the role of ICT in facilitating personalized and interactive learning experiences, promoting student engagement, and fostering critical thinking skills. This work adds to the current conversation on how higher education is changing in the digital age and provides useful suggestions for instructors, administrators, and legislators who want to maximise the use of ICT in the classroom.